Canker of Eucalyptus grandis and E. saligna in Surinam caused by Endothia havanensis - Boerboom, J.H.A.; Th Maas, P.W. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
In 1965, a serious fungal disease causing trunk cankers and death was detected in Surinam on Eucalyptus grandis and E. saligna trees planted in 1962. In 1967, after my reconnaissance in established plantations of these species, it was determined that the disease was present in all localities where they had been introduced. Isolation, inoculation and identification proved that the causal agent of the disease is the bongo Endothia havanensis.